The characteristic of porosity in Al-SiC metal-matrix composite under different milling time - Nozie, Abdullah; Shahruddin, Mahzan; Ade Firdianto; Norashida, Arsat; Darwin, Sebayang; Al Imran, Ismail (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.